Exploiting molecular probes to perform near‐infrared fluorescence‐guided surgery. Issue 4 (8th August 2020) - Wu, Yifan; Zhang, Fan
Abstract: Near‐infrared (NIR) fluorescence imaging can provide real‐time navigation for surgeons to discriminate boundaries between lesions and healthy tissue, which serves as a promising tool to enhance precise diagnosis and accurate excision during surgery. Molecular probes with NIR fluorescence can visualize diseased tissue in deep penetration with improved signal‐to‐noise ratio, which considerably encourages the active participation of NIR fluorescence‐guided surgery in the operating room. Although a great quantity of fluorescent probes has been employed in clinical trials, the U.S. Food and Drug Administration only approves an extremely narrow number of contrast agents for clinical use so far. Currently, there remain two significant problems to be addressed in surgical resection: accurate identification of diseased tissue and the preservation of adjacent vital structures. Here, molecular probes with NIR fluorescence are systematically reviewed to offer possible solutions to these two problems. Targeting strategies of fluorescent probes are introduced, where the strengths and weaknesses of each strategy are presented. Advances in fluorescent probes for the imaging of vital structures, such as nerve and ureter, are also summarized in this review. It is convinced that NIR fluorescence‐guided surgery has the potential to improve current surgical resection and ameliorate the postoperative outcomes of diverse diseases. Abstract : Near‐infrared (NIR) fluorescence imaging can provide real‐time navigation for surgeons to discriminate boundaries between lesions and healthy tissue, which serves as a promising tool to enhance precise diagnosis and accurate excision during surgery. Although a great quantity of fluorescent probes has been employed in clinical trials, the U.S. Food and Drug Administration only approves an extremely narrow number of contrast agents for clinical use so far. This review affords a comprehensive summary to help understand the NIR molecule probes for fluorescence‐guided surgery in both the aspects of identification of diseased tissue and preservation of healthy tissue, where targeting strategies of fluorescent probes are introduced, followed by the advances in fluorescent imaging of vital structures using NIR molecular probes.